Analisis Bahaya terhadap Civitas Akademika: Studi Kasus di sebuah Kampus Universitas Swasta - Nathanael Andrew Hotma; I Nyoman Sutapa; Benedictus Rahardjo (Jurnal Titra, 2020)
Occupational health and safety is an important aspect to be considered by company, also in university. The academic community, which is active in the campus area cannot be separated from the risk of work accidents. This research was done at a private university that was established in Surabaya, East Java. With the extent of the area of the university, it can be possible to pose a potential hazard. Work accidents may occur because of the hazards that have not been identified at the campus area. Therefore, a Hazard Identification Risk Assessment and Risk Control (HIRARC) is needed to identify potential hazards at the campus area. Hazard identification is carried out to determine various potential hazards found at the campus area. After identifying the hazards, then it will carry out a risk assessment. The results of hazard identification and risk assessment at the campus area obtained 164 in the low risk category, 8 in the medium risk category, and 8 in the high risk categories. Every risk found will be carried out to risk control. Risk control will be controlled by means of elimination, substitution, administration, design, and use of personal protective equipment (PPE).